Wetlands for water pollution control / Miklas Scholz - Scholz, Miklas
The second edition covers the fundamental science and engineering principles relevant to the drainage and treatment of both storm and wastewater. Standard and novel design recommendations for predominantly constructed wetlands and related sustainable drainage systems are also provided to account for the interests of professional engineers and environmental scientists.